2016
DOI: 10.1080/09540121.2016.1259449
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of sexual-risk behaviors among young black MSM: implications for clinic-based counseling programs

Abstract: This study applied an 8-item index of recent sexual risk behaviors to young Black men who have sex with men (YBMSM) and evaluated the distribution for normality. The distribution was tested for associations with possible antecedents of sexual risk. YBMSM (N=600), ages 16–29 years, were recruited from an STI clinic, located in the Southern United States. Men completed an extensive audio-computer assisted self-interview. Thirteen possible antecedents of sexual risk, as assessed by the index, were selected for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Condomless anal sex was prevalent among BMSM in our study. This finding is consistent with other reports of prevalent condomless anal sex among MSM [29, 30], including one study that suggests an increasing trend in condomless anal sex among MSM, including BMSM, in recent years [31]. This condomless anal sex trend may be associated with treatment optimism (defined as favorable perceptions regarding the availability or use of antiretroviral therapy in the era of treatment as prevention [TasP]), especially among serodiscordant or unknown status male partners of HIV-positive men; further study is needed.…”
Section: Discussionsupporting
confidence: 94%
“…Condomless anal sex was prevalent among BMSM in our study. This finding is consistent with other reports of prevalent condomless anal sex among MSM [29, 30], including one study that suggests an increasing trend in condomless anal sex among MSM, including BMSM, in recent years [31]. This condomless anal sex trend may be associated with treatment optimism (defined as favorable perceptions regarding the availability or use of antiretroviral therapy in the era of treatment as prevention [TasP]), especially among serodiscordant or unknown status male partners of HIV-positive men; further study is needed.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, Schneeberger et al (2015) notes, problems with alcohol and illicit drug use, as well as promiscuity, were shown to be related to SCE. Crosby, Mena and Ricks (2016) noted that the drunkenness and intoxication of male partners may be one of the strongest antecedents of elevated sexual risk.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, utilizing this model would require assessing their readiness for any kind of change. It is suggested that behavioral interventions with HIV-positive and HIV-negative Black MSM promote strategies for responsible sex, including a sober partner, and opportunities to practice HIV risk reduction strategies through role-playing (Crosby, Mena and Ricks, 2016). Harm reduction works well if a substance user is not yet interested, unwilling, or unable to abstain completely (Weiker, Edgingtom &Kipke, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Sexual behavior and demographic variables were selected on the basis of prior literature examining HIV and sexual risk behaviors. 19,20 Sexual behavior variables were derived from questionnaire items about the number of male partners, discussion of condom use with male sexual partners, having female vaginal partners, perceived risk of acquiring HIV, consistent condom use for both insertive and receptive sex, consistent condom use for insertive sex, and consistent condom use for receptive sex. Most of the sexual behavior variables were derived from responses reported at 3-month followup, which was when the PrEP question was asked.…”
Section: Independent Variablesmentioning
confidence: 99%